Dampak Dampak Bahasa Tubuh dalam Komunikasi Interpersonal:Studi Literatur tentang Pesan Nonverbal - Rahayu, Dewi; Mahfazza, Evva Choirotul; Pratomo, Ozilla Junior; Milad, Khusnu (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
This study examines interpersonal communication in a social context, focusing on its influence on relationships, cooperation, and the effectiveness of interactions. Using a qualitative approach with observation and interview techniques, the research explores how individuals engage in two-way communication in everyday situations. The findings indicate that open, empathetic, and respectful communication contributes to a positive social atmosphere, improves mutual understanding, and reduces potential conflict. These results emphasize the importance of interpersonal communication skills as a key factor in fostering effective and harmonious interactions.